Rationale for referring class II patients for early orthodontic treatment As razões para indicação de tratamento precoce em pacientes de classe II - José Augusto Mendes Miguel; Deise Lima Cunha; Anderson de Albuquerque Calheiros; Daniel Koo (University of São Paulo, 2005)
The tendency of indicating early treatment (before growth spurt) when dealing with Angle Class II cases has been noticed, although there is no definite scientific evidence to justify such decision. The aim of this study was to identify the advantages and disadvantages to this approach and which appliances are used for this purpose. For that purpose, a questionnaire containing full records of a Class II patient was sent to two professors of each Orthodontic graduate program in Brazil (n=96, total 192), from which 107 were properly answered. Results demonstrated that the most used appliances were the headgear (80.4%), maxillary splint (50%) and Bionator (44.4%). The benefits most often quoted were increase of patient self-esteem (78.5%) and reduction in the incidence of incisors trauma (63.6%), while the main disadvantage was saturation of patient compliance (73.8%). Considering early Class II treatment, there is still no unanimity as to treating in one or two stages or in selection of appliances. However, the orthodontists should consider the physical situation of the patient, severity of cases and susceptibility of trauma to the maxillary incisors. It is crucial that updated information is given to parents, in order to justify this approach. A tendência de indicação de tratamento precoce (antes de surto de crescimento) para casos de Classe II de Angle tem sido observada, embora não haja evidência científica para embasar tal decisão. O objetivo deste estudo foi identificar as vantagens e desvantagens da indicação e quais aparelhos são usados no tratamento. Foram enviados questionários (n=192) com a documentação completa de um paciente Classe II para dois professores de cada curso de especialização em Ortodontia no Brasil, os quais 107 foram respondidos. Os resultados demonstraram que os aparelhos mais usados foram: Extra-oral (80,4%), Thurow (50,0%) e Bionator (44,4%). Foram citados como maiores vantagens: aumento de auto-estima do paciente (78,5%) e a redução da incidência de trauma nos dentes incisivos (63,6%), por outro lado a principal desvantagem citada foi a saturação de cooperação do paciente (73,8%). Considerando o tratamento precoce de Classe II não houve o consenso se a correção deveria ser realizada em duas ou em uma única fase e nem a seleção do aparelho a ser utilizado. Porém os ortodontistas deveriam levar em consideração o estado psicológico do paciente, a severidade do caso clínico e a susceptibilidade a trauma dos incisivos superiores. É importante que os responsáveis sejam esclarecidos quanto à necessidade do tratamento precoce.